Fostering the development of the coffee global value chain - Dennis Görlich; Aoife Hanley; Wan-Hsin Liu; Finn Ole Semrau (Kiel Institute for the World Economy (IfW), 2020)
The overarching aim of the study is to investigate the key factors that determine how and how intensively countries can be integrated into the coffee global value chain (GVC) and thus can better reap the globalization benefits. The empirical analysis shows how the international trade in coffee has developed across regions/countries over the past three decades. It provides evidence-based insights into the key determinants of countries' GVC integration in the coffee industry. It discusses countries' functional and product upgrading for their GVC integration. Based on the empirical results obtained, policy implications are derived to support the further development of the coffee GVC. This study serves as a background study for the Coffee Development Report 2020 in preparation by the International Coffee Organisation.
Keywords: F14; O13; O30; 330; coffee; trade; development; global value chain; upgrading